Clinicoetiological profile of patients with gastrointestinal bleed presenting to a tertiary care hospital in Kumaon Region of Uttarakhand - Jayauthrapathi,; Subhash Chandra joshi,; Arun Joshi,; Yatendra Singh, (Asian Journal of Medical Sciences, 2024)
Background: Gastrointestinal (GI) bleed is a common cause of medical emergency resulting in significant morbidity and mortality. GI bleeding can be classified as upper (bleeding source proximal to the ligament of Treitz) and lower (bleeding source distal to the ligament of Treitz). Aims and Objectives: The present study was aimed to determine the current clinicoetiological profile of GI bleeding in Kumaon Region of Uttarakhand. Materials and Methods: All patients presented with GI bleed (GIB) to outpatient department and Emergency department or developed the GIB during hospitalization are managed in intensive care unit (preferably) and high-dependency unit. Results: Both upper and lower GI endoscopy were twice normal in 2.7% of patients (obscure bleeding). On upper GI endoscopy findings showing esophageal varices (45.83%), gastroesophageal varices (8.33%), isolated gastric varices (8.33%), gastric ulcer (8.33%), duodenal ulcer (6.25%), Mallory-Weiss tear (6.25%), erosive gastritis (6.25%), gastric antral vascular ectasia (4.16%), gastric carcinoma (4.16%), and Dieulafoy’s lesion (2.08%). Upper GIB (UGIB) had more mortality than lower GIB, among UGIB variceal bleed having higher mortality than non-variceal bleeding. Conclusion: Unlike the evidence from the west that peptic ulcer is the most common cause of upper gastrointestinal bleeding, we found varices as the common cause, followed by peptic ulcer and erosive gastritis. Hence, the variable spectrum of the etiology of the GIB seen in our country could represent either a true epidemiological difference or reflect skewed access to health care.